Corridas ´meio-fundo´ e ´fundo´ - Monroy, Ricardo Ortiz; Pastori, Marcos Souza; Cardoso, Joadney Lima; Cid, Luiz Fernando Vidal (Revista de Educação Física / Journal of Physical Education, 2021)
Resumo do artigo "Corridas ´meio-fundo´ e ´fundo´".